Greek Churches in the Southern Ukraine in the Making (the Late Eighteenth – the First Half of the Nineteenth Century) - Левченко, Лариса (Український історичний журнал, 2021)
The purpose of the article is to present the results of the study on the history of Kherson and Mykolaiv Greek churches at the end of the 18th and the first half of the 19th cent. The research methodology is based on the generally accepted principles and methods of historical study. Scientific novelty. The history of Greek churches in Kherson and Mykolaiv is covered based on handwritten sources from the state archives of Kherson, Mykolaiv, and Odesa regions. This data is introduced into the scientific body of knowledge for the first time. These sources provided an opportunity to study new facts and names, made conclusions on the role of the Church in the life of Kherson and Mykolaiv Greek communities. Conclusions. The history of the Greek churches reflects the history of the Greeks in the Southern Ukraine under the dominion of the Russian Empire. When the Greeks settled in Kherson, their ties with their country of origin were quite strong. It is clear in the décor of the St. Sophia’s Greek Church, in the wishes to have the priests serving in Greek. The Russian government tended to take the Greek citizens under control with the help of the Russian Orthodox Church. The Greek priests obeyed the regulations of the Russian Church. By the time when the Greeks reached Mykolaiv, their ties with their native land had become weaker. The Greeks serving in the Black Sea Navy were hardly interested in the St. Nicholas Greek Church construction because the Admiralty Cathedral satisfied their religious needs. These Greeks were subjected to assimilation faster than their compatriots not serving in the Navy. The Mykolaiv community of civil Greeks was insolvent and could not build their Church without government aid and the donations of other nationalities’ representatives. The lack of budget instigated a search for funds, disputes on moneyrelated issues, and mutual recriminations of fraud. The assimilation of the civil Greeks manifested in the architecture of the Mykolaiv Greek Church, built as a smaller copy of the Admiralty Cathedral, in the Russian names of the Greeks who were parishioners of the Greek Church, and in the control that the Russian priests had over it. The history of Kherson and Mykolaiv Greek churches is different from the history of the Odesa Holy Trinity Church that became a shelter for participants of the movement for Greek statehood. The Greek churches not only helped the Greeks integrate into a foreign environment and preserve national culture but also promoted their assimilation.